2009
DOI: 10.3184/095422909x466095
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous speciation of chromium by spectrophotometry and multicomponent analysis

Abstract: A simple, fast and sensitive spectrophotometric method for the simultaneous determination of Cr(III) and Cr(VI) in effluents and contaminated waters using a UV-visible spectrophotometer, which operates with an advanced software for multicomponent analysis, is proposed. The method consists in the complexation of Cr (III) with EDTA and reaction of Cr(VI) with diphenylcarbazide (DPC). Variables, such as pH and colour stability time, were studied. The effect of concomitant ions on the simultaneous Cr(III) and Cr(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
(31 reference statements)
1
12
0
4
Order By: Relevance
“…Melaku et al [13] found Cr(VI) concentration in the range 25.1-45.5 ppb in wastewater samples, attributed to effluent discharges from tanneries (Table 3). In another study [14] Cr(VI) concentrations in industrial effluent were found in the range 1.2-6.7 ppm ( Table 3). The reported higher concentrations vis-à-vis current studies were attributed to the use of Cr in the tanning industries.…”
Section: Cr +6 Concentrations Vis-à-vis Studies From Wastewatermentioning
confidence: 90%
“…Melaku et al [13] found Cr(VI) concentration in the range 25.1-45.5 ppb in wastewater samples, attributed to effluent discharges from tanneries (Table 3). In another study [14] Cr(VI) concentrations in industrial effluent were found in the range 1.2-6.7 ppm ( Table 3). The reported higher concentrations vis-à-vis current studies were attributed to the use of Cr in the tanning industries.…”
Section: Cr +6 Concentrations Vis-à-vis Studies From Wastewatermentioning
confidence: 90%
“…Samples of the mixtures were taken out at regular times and were centrifuged immediately (4000 rpm) for <3 min. The amount of chromate in the isolated supernatant ( C t ; mmol/L) was determined with UV-visible spectrometry according to the experimental method described by Soares et al (2009). The quantity of chromate retained ( q t ; mmol/g) was deduced from equation 1: where C o (mmol/L) is the initial concentration of chromate, V is the volume of solution (L) and m is the weight of adsorbent (g).…”
Section: Methodsmentioning
confidence: 99%
“…20,26,27 Cd <LD 0,2 (1) Pb <LD 0,5 (1) Cr(III) 764±10 (2) 1,0 (1) Zn 2,0±0,3 5,0 (1) Cr(VI) 6±1 (2) 0,1 (1) Dureza (3) 1596±265 ------------ (1) Valores máximos permissíveis para efluentes segundo a resolução CONAMA nª 430. 31 (2) Valores obtidos por Soares et al 32 pH=9,6±0,4. Estão em negrito os resultados que ultrapassaram os VMPs.…”
Section: Caracterização Do Efluente De Curtumeunclassified